2019
DOI: 10.9734/jamcs/2019/v34i1-230201
|View full text |Cite
|
Sign up to set email alerts
|

Secure Electronic Voting Using a Hybrid Cryptosystem and Steganography

Abstract: Conventional voting techniques have been employed over the years in most elections. However, each of these techniques has attendant short comings. The existing conventional voting systems have been subjected to gross abuse and irregularities. Electronic voting (e-voting) which is emerging as an alternative to these conventional voting systems, though highly promising, is not also totally free of flaws; information security issues bordering on privacy, integrity and verifiability of the electronic ballots caste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…RSA is one of the oldest and among the most used encryption algorithm. The algorithm was developed in 1977 by three Massachusetts Institute of Technology researchers, Okediran et al [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…RSA is one of the oldest and among the most used encryption algorithm. The algorithm was developed in 1977 by three Massachusetts Institute of Technology researchers, Okediran et al [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results showed that the proposed MQPC secured e-voting system generally performed better compared to the ECC and RSA based ones. Similarly, [29] developed a secure electronic voting system using a hybrid cryptosystem and steganography. The security scheme was based on a hybrid Rivest-Sharma-Adelman (RSA) algorithm and Advance Encryption Standard (AES) algorithm with Least Significant Bit (LSB) algorithm for securing ballot information and to tackle the problems of privacy, verifiability and integrity.…”
Section: Electronic Voting Systemmentioning
confidence: 99%
“…This includes following the laws regarding the establishment and maintenance of an accurate and transparent system. They also have to ensure that the process is conducted in compliance with the requirements of the law and protects the right of voters [7].…”
Section: Figure 1 Traditional Approach Of Votingmentioning
confidence: 99%